Home-based training program during the SARS-CoV- 2 quarantine: training load, motivation, and wellbeing in professional elite female basketball players - Moscaleski, L.; Paludo, A. C.; Panissa, V. L.; de Lima, S. I.; Okano, A. H.; Moreira, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: due to the quarantine caused by the Coronavirus disease 2019 (COVID-19), professional team-sports adapted their training routine to maintain the athletes' performance and minimize the negative emotional effects. The purpose of the present study was to describe a home-based training program and extra-activities applied during the quarantine in elite professional female basketball players, and to compare the internal training load (ITL), session rating of perceived exertion (s-RPE), motivation, and wellbeing responses before and during the quarantine. METHODS: nine female elite players (25.7 ± 7.0 years; 180.0 ± 8.0 cm; 79.0 ± 11.0 kg) belonging to a professional basketball team performed a home-based training program during the quarantine. ITL, s-RPE, training motivation, and wellbeing were examined before (phase 1), at the beginning (phase 2), and during (phase 3) of the quarantine. RESULTS: ITL was higher (main effect) in phase 1 (449.5 ± 62.8 a.u.) compared to phase 2 (265.5 ± 39.0 a.u.) and phase 3 (423.1 ± 18.7 a.u.); s-RPE was higher in phase 1 (4.50 ± 0.63 a.u.) compared to phase 2 (3.8 ± 0.6 a.u.), but not to phase 3 (4.37 ± 0.79 a.u.). Motivation was higher in phase 1 (3.6 ± 0.3 a.u.) compared to phase 2 (2.3 ± 0.6 a.u.) and phase 3 (2.4 ± 0.5 a.u.). CONCLUSIONS: in conclusion, the results of the study demonstrated that extra-activities involving online athletes' socialization were implemented to rouse the motivation, but the quarantine period induced a reduction in ITL and influenced the player's training motivation.